Review: Down’s syndrome- causes and clinical manifestation - Rawaa Najim Alkhamessi; Mustafa K. Al-Bayaty; Hind tahseen Ibraheem (Genius Publishing Group, 2023)
One of the most frequent disorders, Down syndrome (DS), has enormous social and medical consequences. A variety of features have been linked to DS, including congenital heart abnormalities, leukemia, Alzeihmer's illness, and Hirschsprung disease. Affected to differing degrees by various qualities are people with DS. Determining the cause of this diversity is thus a significant issue for about 1 in 800 infants. It is related to abnormalities in several physiological systems, some of which might cause serious and fatal issues. The important factors to take into account when visiting kids with Down syndrome and the clinical problems associated with the condition will be covered in this article
Keywords: Down syndrome; DS; Trisomy